Impact of Anxiety on Medication Adherence in Cardiovascular Disease: A Comprehensive Review - Rathod, Samarth R.; Raval, Dipak H.; Kumar, Ashok (Journal of Pharmacy Practice and Community Medicine)
Cardiovascular Diseases (CVD) are a major cause of illness and death worldwide. Medication adherence is vital for managing these diseases. Psychological factors, especially anxiety, greatly affect adherence in this group. This review collects current evidence on the connection between anxiety and medication adherence in cardiovascular patients. A wide literature search was done to gather information on anxiety rates, biological and social factors, assessment tools, and treatment strategies. Anxiety is common among CVD patients and harms medication adherence through emotional and thinking processes. Important demographic and clinical factors influence this connection. Psychological and technology-assisted treatments show promise in improving adherence and patient outcomes. Regular anxiety screening and care models that combine mental health and cardiovascular services are crucial for improving medication adherence. Future research should focus on culturally appropriate interventions and using digital health tools to boost adherence and quality of life for CVD patients.
Keywords: Anxiety; Cardiovascular Disease; Cognitive Behavioral Therapy; Medication Adherence; Patient Compliance